Plane Waves and Fundamental Solutions in Heat Conducting Micropolar Fluid. (13th July 2016) - Kumar, Rajneesh; Kaur, Mandeep
Abstract : In the present investigation, we study the propagation of plane waves in heat conducting micropolar fluid. The phase velocity, attenuation coefficient, specific loss, and penetration depth are computed numerically and depicted graphically. In addition, the fundamental solutions of the system of differential equations in case of steady oscillations are constructed. Some basic properties of the fundamental solution and special cases are also discussed.